Features influence of social factors on the formation of neurasthenia - Astaf'jeva, G. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article is devoted to the investigation of influence macro- and microsocial factors on forming neurotic disorders. Cleared up specification of modern macrosocial and microsocial factors. Established the psychological characteristics in the family of the patient with neurotic disorders. Investigated specific family relations for every type of neurotic disorders. A complex examination used in the work permitted to create the model of psychotherapy which contains specific founded characteristics.
Keywords: neurotic disorders; macrosocial factors; microsocial factors; social and psychological characteristic; psychopathological psychological characteristic